2021
DOI: 10.3390/ijms22094460
|View full text |Cite
|
Sign up to set email alerts
|

Altered Metabolism in Glioblastoma: Myeloid-Derived Suppressor Cell (MDSC) Fitness and Tumor-Infiltrating Lymphocyte (TIL) Dysfunction

Abstract: The metabolism of glioblastoma (GBM), the most aggressive and lethal primary brain tumor, is flexible and adaptable to different adverse conditions, such as nutrient deprivation. Beyond glycolysis, altered lipid metabolism is implicated in GBM progression. Indeed, metabolic subtypes were recently identified based on divergent glucose and lipid metabolism. GBM is also characterized by an immunosuppressive microenvironment in which myeloid-derived suppressor cells (MDSCs) are a powerful ally of tumor cells. Incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 103 publications
0
13
0
Order By: Relevance
“…Loss of CCR2 expression resulted in a reduced outflow of MDSCs in the bone marrow, thereby reducing GBM infiltration of these cells. Other studies demonstrated that CCL2 mediates the migration and accumulation of MDSCs at tumor sites, which not only inhibits the killing function of natural killer (NK) cells and the anti-tumor immune effect of T cells but also promotes the development of Tregs and limits the maturation of DCs, thereby inhibiting innate and adaptive immunity ( 37 39 ). MDSCs can use metabolic pathways to mature from bone marrow precursors owing to their high glycolysis flux, and this process indirectly leads to effector T-cell inhibition through the consumption of carbon sources ( 40 ).…”
Section: Immunosuppressive Cells In the Tme Contribute To Gbm Progres...mentioning
confidence: 99%
“…Loss of CCR2 expression resulted in a reduced outflow of MDSCs in the bone marrow, thereby reducing GBM infiltration of these cells. Other studies demonstrated that CCL2 mediates the migration and accumulation of MDSCs at tumor sites, which not only inhibits the killing function of natural killer (NK) cells and the anti-tumor immune effect of T cells but also promotes the development of Tregs and limits the maturation of DCs, thereby inhibiting innate and adaptive immunity ( 37 39 ). MDSCs can use metabolic pathways to mature from bone marrow precursors owing to their high glycolysis flux, and this process indirectly leads to effector T-cell inhibition through the consumption of carbon sources ( 40 ).…”
Section: Immunosuppressive Cells In the Tme Contribute To Gbm Progres...mentioning
confidence: 99%
“…In brain tumor patients, immunological dysfunction is a major obstacle to immunotherapy ( 155 ). Some infiltrating immune cells in the tumor microenvironment such as Treg cells ( 162 ), myeloid-derived suppressor cells ( 163 ), etc. are also engaged in immunotherapy resistance.…”
Section: Ferroptosis In Therapy Of Gliomamentioning
confidence: 99%
“…GBM’s poor prognosis has been attributed mainly to its high biological complexity, which is insufficiently understood [ 6 ]. The multiple genetic alterations in GBM confer several biological advantages, such as treatment resistance, high proliferation and metabolic adaptations that allow modulation of the tumor microenvironment (TME) [ 7 ]. In this context, mutations in the active site of isocitrate dehydrogenase 1 (IDH1), a catalytic enzyme that produces alpha-ketoglutarate (α-KG) by oxidative decarboxylation of isocitrate [ 8 ], have been related to a better prognosis in glioma patients.…”
Section: Introductionmentioning
confidence: 99%